Challenges in Implementing Restorative Justice for Children with Special Needs in Bukittinggi: The Role of Investigators and Third Parties - Sofyan Sofyan; Yuda Widodo; Naufal Ilham Ramadhan; Rahmiati Rahmiati; Deddi Fasmadhy Satiadharmanto (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Restorative approach in family law aims to restore balance and justice, especially for special needs children and their families. However, the implementation of this approach often faces various significant challenges. This article discusses the main issues faced by third parties including reporters of domestic violence by the heads of neighborhood associations, school teachers of special needs children, politicians, community groups, local online media reporters, police investigators, lawyers, and other relevant institutions when they fail to effectively implement corrective actions. This research utilizes both empirical and normative legal approaches to explore the factors hindering the success of the restorative approach and to formulate effective solutions. The research findings indicate that the main obstacles in the implementation of the restorative approach include a lack of understanding of the special needs of children, complex bureaucratic procedures, resource limitations, as well as stigma and prejudice against special needs children. This article proposes solutions including specialized training for third parties, simplification of bureaucratic procedures, increased resources, and anti-stigma campaigns. By implementing these solutions, it is hoped that the restorative approach can be more effective in restoring balance and justice for special needs children and their families. This article is expected to provide useful insights for family law practitioners and policymakers in efforts to improve access to justice through the restorative approach.